PENGELOLAAN PEMBELAJARAN SENTRAPADA ANAK USIA DINI DI KELOMPOK BERMAIN UNIVERSAL ANANDADESA PURWOKERTO KECAMATAN PATEBON KABUPATEN KENDAL - GHOFUR, ABDUL, Prof. Dr. Sutama (2017)
in KB Universal Ananda Village Patebon Purwokerto District of Kendal. Thesis. Surakarta Muhammadiyah University Graduate Program. 2017. The purpose of this study was to describe (1) the planning of learning centers in KB Universal Ananda Village Patebon Purwokerto District of Kendal, (2) the implementation of the implementation of the Universal family planning centers at Ananda Village Patebon Purwokerto District of Kendal. This type of research is qualitative. This research was conducted in KB Universal Ananda Village Patebon Purwokerto District of Kendal. The main subject of study is the head of KB, teachers, and parents. Methods of data collection using interviews, observation, and documentation. Analysis of data starting from (1) Data Collection, (2) data reduction, (3) display the data, and (4) conclusion. Test the validity of the data using a credibility, tranferabilitas, confirmability and dependability. The results of this study were (1). Teachers have prepared a theme and make a plaything of education in an integrated manner to develop all aspects of religious moral values, physical, motor, cognitive, social, emotional, language and art. Before implementing teacher learning has drawn up plans Semesrean Program (promissory notes), plan learning program Weekly (RPPM) and Plan Daily Program (RPPH) as a reference implementation of learning. (2) The teacher has been managing environmental footing play safely, comfortably to encourage children to express, interact with friends and developmentally appropriate environment and the child can develop independence and confidence. Teachers have prepared a variety of game play as well as organizing tool for the coming child. Stepping before the play has been performed with the marching activity by forming a circle while the theme of learning and making rules. In the main foothold teacher as a facilitator to encourage and support the children involved optimally to cultivate curiosity and record observations adekdot and child development activities footing after main teacher assessment to determine the absorption learning activities undertaken by recalling technique.